REFORMULASI SISTEM POLITIK YANG ADIL DALAM MEWUJUDKAN KETAHANAN HUKUM NASIONAL - Devra, Desi Devrika (Jurnal Pengabdian Kompetitif, 2025)
The application of Pancasila values in the political system is essential to achieving social justice, with the second principle emphasizing human rights and the fifth principle emphasizing social justice for all citizens. A just political system must be based on the principles of democracy, transparency, and accountability, as regulated by various legal instruments such as Law Number 7 of 2017 on General Elections and Law Number 30 of 2014 on Government Administration. Strengthening national legal resilience requires reforms that include enhancing the capacity of law enforcement agencies and strengthening oversight and accountability, in accordance with Law Number 15 of 2004. This study also highlights the importance of Pancasila-based legal education and public participation in reinforcing national legal resilience. Overall, the study concludes that the implementation of Pancasila values and relevant legal regulations is a key step in establishing a fair and sustainable political system in Indonesia